Relationship between Contract of Carriage of Goods and Bill of Lading - Bazghadze, Tamar (Journal of Law, 2022)
International commercial transaction, in particular, several legal relationships that create entire net of this transaction, include numerous parties and documents. One of the main documents of this transaction is bill of lading. Bill of lading, on the one hand, includes the provisions of contract of carriage and serves as main evidence of this contract; on the other hand, bill of lading grants third party (the consignee) with the right over the cargo. First stage of international commercial transaction is contract for the international sale of goods, parties of which are seller and buyer. United Nations Convention on Contracts for the International Sale of Goods (CISG) refers to the obligations of the seller that include to deliver the goods to the buyer. The obligations of the seller might also include conclusion of the contract of carriage, if the parties agree on such through the contract of sale of goods. For this purposes the seller has to provide carriage of the goods, in handing the goods over to the first carrier for transmission to the buyer. Accordingly, CISG, beyond the general obligations of the seller, refers to the transport documents and imposes the obligations upon the seller for the purposes of the contract of carriage. Subject of research of this article is bill of lading, used in international carriage of goods by sea. Legal relationships related to this transaction are regulated through International Convention for the Unification of Certain Rules of Law relating to Bills of Lading, as amended by the Brussels Protocol (the Hague-Visby Rules), and by the United Nations Convention on the Carriage of Goods by Sea of 1978 (the Hamburg Rules). The article also refers to United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (hereinafter – the Rotterdam Rules), that is not yet in force because of unsufficient number of ratifications. Parties of contract for international sale of goods are the seller and the buyer. As for the contract of carriage, parties of it are the shipper and the carrier. Transport documents are initial part of international carriage of goods and issuing of them, usually, takes place after conclusion of contract for international sale of goods and contract of carriage. Commercial transaction depends on accuracy of the transport documents that are used in international carriage of goods. Bill of lading evidences provisions of contract of carriage and also, does include some of them. Contracts preceding the bill of lading might be concluded in verbal form, through electronic communications or by conduct, without clear acceptance and signature. In such cases the bill of lading might have contractual nature and serve as a contract. Also, bill of lading, as the document of title, transfers contractual rights to the third party – the consignee, creating grounds for legal relationship between the consignee and the carrier. Whereas the contract of carriage does not exist or the bill of lading does not comply to it, the bill of lading is the only document to determine the rights of the consignee and obligations of the carrier before him. All of the abovementioned issues make clear functional diversity of the bill of lading that are beyond being only receipt of goods and prima facie evidence of the contract of carriage. Accordingly, accuracy of the information contained in bill of lading shall be provided by the parties, especially during the development of it as far as this is the main source to indicate the following: will of the parties involved in commercial transaction, provisions of contract of carriage, agreement of the parties on allocation of the rights and obligations between them, liable parties and liability/limitation of liability.